What is the Policy of Providing School Operational Funds in Bengkulu City, Indoneisa, during the Covid-19 Pandemic? - Sugeng Suharto (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out the implementation of school operational assistance fund management (BOS) in Indonesia. This study involved BOS funds in 2019, 2020, and 2021. The study uses qualitative descriptive methods and also uses and collects secondary data. Secondary data is collected using documentation techniques. In analyzing data, researchers use data reduction data, data presentation, and verification data. The results showed that there were 646 schools that received BOS funding with a total of more than 28.8 billion funds, distributed to 96,870 students. Furthermore, accountability, transparency, and effectiveness of the management of school operational assistance funds (BOS) Bengkulu in accordance with the provisions of the Regulation of the Minister of Education and Culture (Permendikbud) Number 26 of 2017.